Splenic mycotic aneurysm complicating Streptococcus salivarius mitral valve endocarditis - R. W. P. M. R. A. S. Rajapaksha; K. L. R. Kalupahana; U. Eranthaka (Sri Lanka College of Internal Medicine, 2023)
A mycotic aneurysm is a serious, life-threatening complication occurring in 3-10% of patients with infective endocarditis. Splenic artery mycotic aneurysm is an extremely rare complication to occur, and it has not been previously reported with Streptococcus salivarius infective endocarditis. We are reporting a case of a 57-year-old woman with Streptococcus salivarius mitral valve endocarditis, complicated by a leaking splenic mycotic aneurysm which was successfully managed with embolisation. It is important to consider this rare complication in infective endocarditis patients with an acute abdomen.